To What Extent do the Findings of Laboratory-Based Spatial Attention Research Apply to the Real-World Setting of Driving? - Ho, C; Gray, R; Spence, C (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper provides a critical review of laboratory-based studies of spatial attention. We highlight a number of ways in which such studies fail to capture the key factors/constraints that have been shown to give rise to an increased risk of vehicular accident in real-world situations. In particular, limitations that are related to the design of the attentional capture task itself and limitations that are concern the demographic and current state of the participants tested in these laboratory studies are discussed. A list of recommendations are made concerning those areas in which laboratory-based spatial attention research could focus on in the future in order to make sure that their results are more relevant to those working in an applied setting, and thus, enhance translational research. © 2014 IEEE.